1923 N.H. Laws 138, § 3 - (:unkn) unknown (My University, 1923)
§No unnaturalized foreign-born person and no person who has been convicted of a felony against the person or property of another shall own or have in his possession or under his control a pistol or revolver, except as hereinafter provided
Keywords: POSSESSION - DANGEROUS PERSONS